Cognitive bias in clinical large language models - Arjun Mahajan; Ziad Obermeyer; Roxana Daneshjou; Jenna Lester; Dylan Powell (npj Digital Medicine)
Cognitive bias accounts for a significant portion of preventable errors in healthcare, contributing to significant patient morbidity and mortality each year. As large language models (LLMs) are introduced into healthcare and clinical decision-making, these systems are at risk of inheriting – and even amplifying – these existing biases. This article explores both the cognitive biases impacting LLM-assisted medicine and the countervailing strengths these technologies bring to addressing these limitations.